2019
DOI: 10.1007/s00586-019-05988-1
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the natural course and clinical relevance of Modic changes over 2 years following lumbar limited discectomy: analysis of prospective collected data

Abstract: Purpose Few retrospective studies have addressed Modic changes (MC) following lumbar spine surgery, though it is usually assumed that MC increase in grade and incidence. To test this conventional wisdom, we investigated the natural course of MC following primary lumbar limited discectomy with two-year follow-up. In addition, a possible clinical relevance to those changes was assessed. Methods The data of the control group (278 subjects) of a prospective randomized, controlled trial (RCT) were evaluated retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…Modic changes do not upgrade from Modic 0 to Modic 3 in a simple manner as predicted. Recently, Bostelmann et al [29] observed upgrading and downgrading of Modic changes in patients who were followed up for 2 years after lumbar discectomy. However, our knowledge regarding Modic changes in children and adolescents is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…Modic changes do not upgrade from Modic 0 to Modic 3 in a simple manner as predicted. Recently, Bostelmann et al [29] observed upgrading and downgrading of Modic changes in patients who were followed up for 2 years after lumbar discectomy. However, our knowledge regarding Modic changes in children and adolescents is still limited.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of cases with MC, previous studies have also reported successful results. Bostelmann et al 24 retrospectively analyzed the clinical data of 278 patients undergoing discectomy and they found that different types of MC were not associated with clinical outcomes. Udby et al 23 conducted a 2-year follow-up study and found that MC was not associated with quality of life, pain, or patient satisfaction at 2 years after discectomy.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that it may be associated with the increase in fatty degeneration of the vertebral subchondral bone marrow caused by lumbar surgery [9]. However, a recent new insight tends to consider that the pattern of MCs following lumbar discectomy is complex and not simply increasing [8].…”
Section: Incidence Of New Mcs After Surgerymentioning
confidence: 93%
“…For patients with lumbar degenerative disease, several common surgeries including discectomy, sequestrectomy, decompression, and fusion are currently proven safe and effective. However, these surgical procedures seem to directly alter the biomechanical forces on a microstructural level and predispose the adjacent vertebral bodies to MCs [8], especially in the case of a disrupted disc/an injured annulus fibrosus. The influence of different surgical techniques on endplate changes may be different [6].…”
Section: Introductionmentioning
confidence: 99%